The influence of rainfall on the mode shifting and departure time of commuters the case of Ortigas CBD workers - Sunga, Abigail P. (School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
Heavy rainfall in Metro Manila especially during peak periods causes paralysis in the overall transportation system. Among the most affected by the disruptions caused by bad weather are the working commuters who then attempt to mitigate the effects of these delays by modifying their trip decisions. This research presents an analysis of how rainfall influences the travel mode choice and departure time of work-to-home commuters from Ortigas CBD. The primary data collection for this research was done by administering a questionnaire survey in December 2016, gathering information from total of 300 respondents. The respondents were mostly young workers from ages 21 to 30 with a mean income of 25,000. The analysis using Wilcoxon test of significance reveals that the fare, travel time, walking time, waiting time, as well as perceptions of service reliability, comfort and safety and security of the transport modes servicing Ortigas CBD significantly change during heavy and intense rainfall compared to no rain conditions. Fare and travel time are the main considerations of the respondents in choosing their preferred mode during no rain and light rainfall condition but their priorities shift toward comfort and service reliability during heavy and intense rainfall consequently affecting their mode choice. The level of switching to alternative public transport modes is at 17.67%, 39.33% and 44.67% during light rainfall, heavy rainfall and intense rainfall respectively, with P2P buses, ordinary taxis, Grab taxis and GrabCar/Uber services gaining patronage while aircon buses, jeepneys, FX/vans and MRT-3 lose their passengers. The analysis using binomial logistic regression reveal that commuters choose to shift to another mode during heavy and intense rainfall because of the decrease in the service reliability of their usual mode. Their new modes, on average, offer better services in terms travel time savings, service reliability, comfort and safety and security but incurs a higher cost. At the same time, the percentage of commuters changing their departure time increases sharply from 25% during light rainfall to 67% during heavy rainfall to 72% during intense rainfall mostly leaving their workplace at a later time. Considering mode shifting and change in departure time simultaneously, 63% maintain their mode and departure time during light rainfall but this greatly reduces to 23% and 17% during heavy and intense rainfall. Public transport officials, managers and operators, managers, and operators, especially of those modes losing patronage during these adverse weather conditions, should work on improving the service reliability of their fleet to minimize losing passengers to other modes. The average amount of P627,120.97 per instance of intense rains being spent by working commuters from Ortigas CBD alone provides a sense of the magnitude costs imposed by intense rains to the passengers. Improving the service reliability will greatly help the commuting public go home faster without having to spend too much very rainy day.